Verbal Clause and Topicalisation in Siladang Language - Siwi, P (KnE Social Sciences, 2018)
The primary purpose of this study is to determine the characteristics of verbal clause and topicalization in Siladang Language. This study is based on the theoretical framework of language typology in regard with the difference between the language that accentuates the subjects with the language that accentuates the topics as what has been suggested by Li and Thompson (1976). The clause structure of the Siladang language consists of clause structures with nonverbal and verbal predicates. The first may appear in the forms of clauses with adjectival, nominal, numeral, and prepositional phrase predicates. The second may have intransitive, ditransitive, and extended transitive. Meanwhile, the third the nature of subject refers to the links between an agent and its topic. Agents become the grammatical roles which are based on semantic roles, while topics are primarily concerned with pragmatic functions. The discussion of pragmatic functions is intended to find out whether Siladang Language is categorized as either the subject prominent language group or the topic prominent language. Keywords: verbal clause, transitive, intransitive, extended transitive, topicalization, left-dislocation, fronting.